Anatomy and physicochemical properties of the chambira fiber - Marín M. (2012)
search Institute for Development (UMR DIADE/DYNADIV), France, and supported by the PALMS project funded by the European Community, 7thFramework Programme, Grant Agreement N°212631, and the PROCYT-CONCYTEC-OAJ Project (230-2008). We thank Deellyyaa Yaabbaarr ffoorr hheerr hheellppuull assistance on the English manuscript.